Predictive value of C-reactive protein and clinically relevant baseline variables in sarcoidosis - McDonnell, Melissa J.; Saleem, Mohammed I.; Wall, Deidre; Gilmartin, J. J.; Rutherford, R. M.; O'Regan, Anthony (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: This study aims to examine the predictive and prognostic implications of C-reactive protein (CRP) and clinically relevant baseline variables in determining treatment indication and disease progression in a large clinical cohort of patients with stable sarcoidosis. Methods: A retrospective observational study of 328 sarcoidosis patients attending a regional tertiary referral centre over a 26-year period was performed. Clinical, biochemical, radiological and physiological data were analysed according to a clinically relevant dichotomous cutpoint of CRP. Multiple models of logistic regression were used to determine independent predictors of outcome as defined by indication for treatment with corticosteroids, radiological deterioration and physiological progression. Results: 328/409 (80.2%) sarcoidosis patients had baseline serum CRP measured and were suitable for inclusion. Baseline CRP was elevated in 154 (47%). 178 (54.3%) were prescribed corticosteroid treatment during the disease course. Physiological deterioration was demonstrated in 48 (14.6%) patients and radiological progression in 59 (17.9%) patients. High baseline CRP was strongly associated with Lofgren’s syndrome (p=<0.001) and reduced FVC% predicted (p=0.012). High CRP was found to be a negative predictor of radiological progression (p=0.046). In a sub-analyses of patients without Lofgren’s syndrome (n=223), patients with high baseline CRP were almost twice as likely to receive corticosteroid treatment, OR 1.89 (95% CI 1.04-3.55). Low baseline DLCO% independently predicted the need for corticosteroid treatment (p=<0.001) and physiological decline (p=0.045). Conclusions: Elevated baseline CRP in sarcoidosis is associated with a good prognosis and is a negative predictive indicator of radiological progression. In patients without Lofgren’s syndrome, high CRP and low DLCO% at presentation may identify a subset of patients more likely to develop physiological progression who may benefit from early systemic treatment.